When Do Students in Low-SES Schools Perform Better-Than-Expected on a High-Stakes Test? Analyzing School, Teacher, Teaching, and Professional Development Characteristics. (October 2020) - Fischer, Christian; Fishman, Barry; Levy, Abigail Jurist; Eisenkraft, Arthur; Dede, Christopher; Lawrenz, Frances; Jia, Yueming; Kook, Janna Fuccillo; Frumin, Kim; McCoy, Ayana
This empirical study analyzed data from 638 teachers and 11, 800 students in low-socioeconomic status (SES) urban schools (and schools with urban characteristics) exploring associations of school, teacher, teaching, and professional development characteristics toward student performance on the revised Advanced Placement (AP) Biology and AP Chemistry examinations. The analyses indicated that districts per-student funding allocations, the days of instruction, teachers' knowledge and experience, and some aspects of teachers' professional development participation were significantly associated with student performance on AP science examinations that was better than predicted by students' Preliminary Scholastic Aptitude Test (PSAT) scores.